INTERNALISASI KEMAMPUAN MENGHAFAL SISWA MENGGUNAKAN MEDIA FLASHCARD MELALUI EKSTRAKURIKULER TAHFIDZ DI MADRASAH IBTIDAIYAH NURUL ISLAM MAYANGAN - Wulandari, Diana; Khosiah, Nur; Sholeha , Imro Atus (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2025)
This study aims to evaluate the impact of using flashcards as a medium in the internalization of students' memorization abilities through the Tahfidz extracurricular program at MI Nurul Islam, located in Kelurahan Mayangan, Kecamatan Mayangan, Probolinggo City. Employing a qualitative descriptive approach, the research collected data through observation, interviews, and documentation to gain an in-depth understanding of the effectiveness of flashcards in the Tahfidz teaching process. The research was conducted on May 20, 2024, and involved various data sources, including recordings of the learning process, student evaluation results, curriculum documents, and guidelines for using flashcards. The informants included teachers, students, parents, and school administrators. Data analysis techniques involved data reduction, data presentation, and conclusion drawing. Data reduction was carried out by noting and summarizing important information, while data presentation facilitated the understanding of research results through explanations and diagrams. Conclusions were drawn to summarize the research findings and present them meaningfully. Data validity was ensured through triangulation techniques, comparing interview results, observations, and documentation to ensure accuracy and validity. The research findings are expected to provide valuable contributions to the development and improvement of the Tahfidz extracurricular program and the effectiveness of using flashcards in enhancing Quran memorization skills among students at MI Nurul Islam.